Bibliometric insights into the South African Journal of Animal Science: Trends and contributions - C McManus; MM Scholtz; V Peripolli; D Pimentel; VS Junqueira; CB Banga; F Pimentel (South African Journal of Animal Science)
Articles (1558 in total) published in the South African Journal of Animal Science (SAJAS) were identified in the Scopus, Scielo, and InCites (Web of Science) databases. The Scimago Journal Rank (SJR) indicator for SAJAS in 2022 was 0.33, with a journal H-index of 37. The journal is in the Q3 quartile, reaching Q2 in 2014 and 2017, and has the 2nd highest SJR in African Animal Science and Zoology journals. The InCites average Category Normalised Citation Index is 0.43, with 77% of articles being cited, but varies between research fields, with a score of 0.32 for Agriculture, Environment, and Ecology (85% of published papers), 0.23 for Clinical and Life Sciences (14% of published papers), and 0.44 for Social Sciences. There is a mean of 43 references per article, with each article receiving, on average, 1.1 citations. Most papers are on poultry and ruminants, with fewer papers on wild animals and less prominent farm species. The major breeds studied include Merino sheep and Holstein cattle, with fewer papers on South African breeds. This analysis is important for the journal and its readership as a self-evaluation of the scope and impact of the journal and how this is changing, as well as aiding editors in shaping the journal’s future direction. Citations have decreased over the last 20 years, and international collaborations are few; however, bias in this analysis should be noted, as recent papers and papers not indexed in Scopus have lower numbers of citations. The journal must reaffirm itself as a leading journal for tropical animal production.